Effect of Budget Participation, Individual Capacity, To Managerial Performance At Baitul Mal wa Tanwil (BMT) - Kristianto, Djoko; Ratnawati, Tri (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
A budget is a financial plan that covers a short-term period and is used as a control in an organization. In the preparation of an effective budget requires the ability to predict the future, therefore managers need to prepare a budget properly because the budget is a financial plan that describes all operational activities in a company. This study aims to analyze the effect of budget participation, individual capacity, on managerial performance. The author conducted a survey of managers and administrators involved in budgeting. The total respondents were 64 consisting of managers and administrators (BMT) Baitul Mal wa Tanwil. Hypothesis testing in this study using multiple linear regression. The results showed that Budget Participation, effect on Managerial Performance at Baitul Mal wa Tanwil (BMT). While Individual Capacity, has no effect on Managerial Performance at Baitul Mal wa Tanwil (BMT)